Analisis Volume Usaha Koperasi dan Omzet Usaha Mikro Kecil dan Menengah terhadap Pengangguran Melalui Produk Domestik Regional Bruto Se-Kalimantan Selatan - Khan, Mutiara; Saipudin, Saipudin; Muzdalifah, Muzdalifah (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2024)
The general condition of the Open Unemployment Rate in South Kalimantan during 2018-2022 shows relatively increasing findings, especially during the COVID-19 pandemic. The volume of cooperative business and MSME turnover is one of the means that can be used to reduce it through GRDP as a forum that reflects regional economic conditions. This paper aims to make a deeper identification related to the direct and indirect relationship of cooperative business volume and MSME turnover to the open unemployment rate through GRDP in South Kalimantan Province Districts / Cities in 2018-2022. The data used in this study are secondary data collected through documentation methods and processed using quantitative methods with regression panel data to determine the direct influence between variables both simultaneously and partially and with path analysis using the Sobel test to determine the indirect influence between independent variables, namely the volume of cooperative businesses and MSME turnover on the dependent variable, namely the unemployment rate open through the intervening variable is. GRDP. The results of this study show a direct influence of the volume of cooperative businesses, MSME turnover, and GRDP on the open unemployment rate simultaneously. Only partially does MSME turnover significantly affect the open unemployment rate. Meanwhile, the volume of cooperative businesses and MSME turnover directly and partially affect GRDP. There is no indirect influence (through GRDP) on the volume of cooperative businesses or MSME turnover and the open unemployment rate in South Kalimantan Province.